PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, SUMBER DAYA MANUSIA, DAN KINERJA PEGAWAI TERHADAP KUALITAS LAPORAN KEUANGAN - Kadek Dwiyanti Yussilasari; Nur Fitriyah; Endar Pituringsih (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
This study aimed to examine the influence of the implementation of the Government Accounting Standards, human resources competencies and performance of employees on the quality of financial statements presented by the government. Population in this research is the employee at the Ministry of Religious Regional Office of West Nusa Tenggara province amount 126 people. The sampling technique in this study using purposive sampling method, which is only the employees who are responsible for financial management, of budget planning and administration and financial reporting. Data obtained by distributing questionnaires to 77 respondents who fit into the criteria of the sample. Data analysis using Multiple Linear Regression Analysis. The results showed that the implementation of the Government Accounting Standards, human resources competencies and performance of employees have a positive influence on the quality of financial statements. The better the implementation of SAP, the competence of its human resources and employee performance, the higher the quality of government financial reports are produced. The implications of this study explain the importance of the implementation of SAP, human resources competencies and performance of employees to improve the quality of financial statements that can be used as best as possible to making the right decision. So the conflicts that may arise in the agency theory can be minimized.